2020
DOI: 10.3390/antibiotics9030101
|View full text |Cite
|
Sign up to set email alerts
|

Declining Prevalence of Methicillin-Resistant Staphylococcus aureus Septic Arthritis and Osteomyelitis in Children: Implications for Treatment

Abstract: This study sought to assess clinical characteristics and differences in outcomes between children with Methicillin-resistant Staphylococcus aureus (MRSA) and Methicillin-sensitive Staphylococcus aureus (MSSA) osteomyelitis or septic arthritis and whether initial antibiotic regimen affects patient outcomes. We analyzed records of children ages 15 days to 18 years admitted between 2009 and 2016 to two tertiary children’s hospitals who were diagnosed with an osteoarticular infection and had a microorganism identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They found that 76% of the infants who had MRSA bacteraemia cleared the infection after clindamycin treatment ( Greenberg et al., 2020 ). Clindamycin should be considered for inclusion in the initial antibiotic regimen for treating osteomyelitis and septic arthritis because patients whose initial antibiotic regimens included vancomycin had a longer hospitalization compared with those initiated on a treatment regimen of clindamycin without vancomycin ( Weiss et al., 2020 ). However, we found a particularly high rate of clindamycin resistance among bone and joint-derived MRSA isolates (72.73%), and clindamycin is not suitable to be recommended for the empirical treatment of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 76% of the infants who had MRSA bacteraemia cleared the infection after clindamycin treatment ( Greenberg et al., 2020 ). Clindamycin should be considered for inclusion in the initial antibiotic regimen for treating osteomyelitis and septic arthritis because patients whose initial antibiotic regimens included vancomycin had a longer hospitalization compared with those initiated on a treatment regimen of clindamycin without vancomycin ( Weiss et al., 2020 ). However, we found a particularly high rate of clindamycin resistance among bone and joint-derived MRSA isolates (72.73%), and clindamycin is not suitable to be recommended for the empirical treatment of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cefazolin was chosen for empiric MSSA coverage, as our institution, as have many medical centers across the United States, has noted an increased incidence of MSSA as opposed to methicillin-resistant S. aureus (MRSA) in pediatric bone and joint infections. 4 Surprisingly, the tissue biopsy culture resulted in the pure growth of a gram-negative rod, initially identified as Salmonella species, with subsequent identification by the Michigan State Health Department Microbiology Laboratory as Salmonella enterica subsp. enterica serovar Poona ( S. Poona).…”
Section: Case Reportmentioning
confidence: 99%
“…1,2 In children and adolescents, the bones most commonly involved include the long-bones of upper and lower extremities, with osteomyelitis of the vertebral bodies of the spine being much less common, accounting for only 1%–2% of osteomyelitis episodes in children. 3,4 Osteomyelitis is commonly due to pyogenic bacteria with Staphylococcus aureus accounting for 32%–67% of cases among all ages. 1,36 Among pediatric populations, S. aureus and Streptococcus species, including Group B Streptococcus , are the predominate pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus has developed multi-drug resistance toward different antibiotics, especially methicillin (MRSA). MRSA strains include healthcare-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA) aspects which may be an increased risk of spreading the S. aureus infections [ 6 ] ranging from skin to other invasive diseases such as pneumonia [ 7 ], meningitis [ 8 ], sepsis [ 9 ], osteomyelitis [ 10 ], and infective endocarditis [ 11 ]. The newest antibiotic on the market (linezolid (Zyvox)) was introduced to the North American market in 2000 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%